The effect of portfolio-based learning models and self-regulated learning on student’s creative thinking skills on acid and base materials - Rini Alfiahas; Asrial Asrial; Damris Muhammad (Pascasarjana Universitas Negeri Medan, 2020)
The acid and base concepts are fundamental in understanding chemistry taught at senior high schools. The chemistry concepts are generally abstract and sometimes complex. Teachers are required find ways that lead to improve their students understanding. This study aimed to look at the effect of portfolio-based learning model and self regulated learning on students creative thinking skills on acid and base teaching materials. Data of students creative thinking skills were collected with test and self-regulated learning with questionnaire. The data analysed with two-way ANOVA shows that the portfolio-based learning models and students self-regulated learning have a positive effect on the students' creative thinking skills in the material taught. However, both are independent and do not interact each others in affecting the student creative thinking skills.Keywords: Acid and base, Creative thinking skills, Portfolio based learning model, Self regulated learning